LAW ENFORCEMENT AGAINST AIRCRAFT ENTERING THE TERRITORY OF THE UNITED STATES OF THE REPUBLIC OF INDONESIA - Sungkono; Sujono; Bagus Rahmadi Supancana, Ida (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
Law enforcement against unauthorized foreign aircraft entering the territory of the Unitary State of the Republic of Indonesia is a crucial aspect in maintaining air sovereignty and national security. This research examines the legal policies and procedures implemented in dealing with violations by foreign aircraft, as well as the challenges and solutions faced by Indonesian authorities. The main focus of this research includes the identification of relevant national and international regulations and law enforcement mechanisms. The research methods used include legal analysis and case studies of violations that have occurred. Research results show that although Indonesia has a clear legal framework for dealing with violations, its implementation is often hampered by limited resources and the complexity of international diplomacy. The recommendations put forward include increasing law enforcement capacity, improving coordination between relevant institutions, as well as strengthening international cooperation to improve the law enforcement system in the aviation sector. It is hoped that this research can contribute to the development of more effective policies and practices in maintaining Indonesia's air sovereignty.